2014
DOI: 10.4254/wjh.v6.i4.199
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitizers for the treatment of non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the leading cause of liver disease in the Western world and is closely associated with metabolic syndrome, which includes hypertension, central obesity, dyslipidemia and insulin resistance. NAFLD includes a wide spectrum of liver alterations, ranging from simple hepatic steatosis to variable degrees of fibrosis, cirrhosis and even hepatocellular carcinoma. Although the etiology and progression of the disorder remain poorly understood, insulin resistance is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 69 publications
1
37
0
3
Order By: Relevance
“…Insulin-sensitizing therapies are increasingly available, 33,34 and high-risk patients previously benefitted from lifestyle interventions or metformin. 9 Although population-based prevalence data are not available, our results, in line with previous estimates, 5,31 suggest that a large number of obese humans are insulin resistant and may profit from such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-sensitizing therapies are increasingly available, 33,34 and high-risk patients previously benefitted from lifestyle interventions or metformin. 9 Although population-based prevalence data are not available, our results, in line with previous estimates, 5,31 suggest that a large number of obese humans are insulin resistant and may profit from such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although a meta-analysis including 862 patients, 38% of them diabetics, showed that thazolidinediones improve steatosis, hepatocellular ballooning, and inflammatory events, delaying the progression of fibrosis, 21 pioglitazone has been related to multiple adverse effects including bladder cancer, osteoporosis, weight gain, lower limb edema, and congestive heart failure. 22 Because of these adverse effects, other alternative drugs may be of interest. In our pilot study, exenatide combined with metformin achieved the highest percentages of qualitative ultrasonographic improvement in NAFLD, but the difference was not statistically significant, possibly because of the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Two classes of drugs have been shown to correct insulin resistance: biguanides (e.g., metformin) and thiazolidinediones. Metformin, a biguanide that reduces hyperinsulinemia and improves hepatic insulin sensitivity, reduces hepatomegaly and hepatic steatosis in ob/ob mice [109] , but results in human studies have been less impressive [110,111] as in human studies, although ALT improved and liver size decreased, metformin was not consistently found to improve liver histology [110,112] .…”
Section: Insulin Sensitizersmentioning
confidence: 99%